Gamification in E-learning: Bridging Educational Gaps in Developing Countries - Ghoulam, Khalid; Bouikhalene, Belaid; Babori, Abdelghani; Falih, Noureddine (International Journal of Advanced Corporate Learning (iJAC), 2024)
In the field of education, developing countries face numerous challenges, including limited resources, inadequate infrastructure, and a shortage of qualified educators. This research paper explores the transformative potential of gamification in e-learning as a strategic approach to mitigate these challenges and bridge educational gaps in developing countries. The study investigates the impact of integrating gamified elements into the e-learning environment, aiming to enhance student engagement, motivation, and knowledge retention. The research employs a mixed-methods approach, combining quantitative analysis of student performance metrics with qualitative insights from educators and learners. The investigation evaluates the effectiveness of gamification in fostering a positive learning experience and addressing specific educational gaps prevalent in developing nations. Additionally, the study examines the adaptability of gamified e-learning platforms to diverse cultural and linguistic contexts, ensuring inclusivity and relevance. The findings of this research contribute valuable insights to the discourse on leveraging technology for educational advancement in resource-constrained settings. By shedding light on the potential benefits and challenges of gamification in e-learning within the context of developing countries, this paper aims to inform policymakers, educators, and researchers on innovative strategies to enhance the quality and accessibility of education. Ultimately, the research seeks to provide practical recommendations for the integration of gamified e-learning approaches, fostering sustainable educational development in the global context.